2020
DOI: 10.1111/febs.15269
|View full text |Cite
|
Sign up to set email alerts
|

USP7‐dependent control of myogenin stability is required for terminal differentiation in skeletal muscle progenitors

Abstract: Satellite cells (SCs) are myogenic progenitors responsible for skeletal muscle regeneration and maintenance. Upon activation, SCs enter a phase of robust proliferation followed by terminal differentiation. Underlying this myogenic progression, the sequential expression of muscle regulatory transcription factors (MRFs) and the downregulation of transcription factor paired box gene 7 (Pax7) are key steps regulating SC fate. In addition to transcriptional regulation, post-translational control of Pax7 and the MRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Finally, because our BioGRID analysis suggested the interaction of TCF7L2 with deubiquitinating enzymes (e.g. USP4), we evaluated the amount of TCF7L2 protein in C3H/10T1/2 MSCs treated with the ubiquitin-specific protease 7 (USP7) inhibitor HBX 41108 (HBX) in proliferating conditions (Colland et al, 2009;de la Vega et al, 2020;Yuan et al, 2018). Treatment with only HBX diminished TCF7L2 protein levels in a time-dependent manner (Fig.…”
Section: Tgf-β Reduces Tcf7l2 Protein Levels By Stimulating Its Degramentioning
confidence: 99%
“…Finally, because our BioGRID analysis suggested the interaction of TCF7L2 with deubiquitinating enzymes (e.g. USP4), we evaluated the amount of TCF7L2 protein in C3H/10T1/2 MSCs treated with the ubiquitin-specific protease 7 (USP7) inhibitor HBX 41108 (HBX) in proliferating conditions (Colland et al, 2009;de la Vega et al, 2020;Yuan et al, 2018). Treatment with only HBX diminished TCF7L2 protein levels in a time-dependent manner (Fig.…”
Section: Tgf-β Reduces Tcf7l2 Protein Levels By Stimulating Its Degramentioning
confidence: 99%
“…injuries triggering acute muscle regeneration in animal models. An example is shown by de la Vega et al [5], who report that important components of the ubiquitin proteasome system are necessary for activation of the myogenic transcriptional programme after myofiber cytotoxic injury. Some of the satellite cells in muscle may also continue to contribute to continued normal postnatal growth and muscle maintenance.…”
Section: Myogenesis During Development and Injurymentioning
confidence: 99%
“…A pro-myogenic effect of DUB activity was recently reported by De la Vega and cols. ( de la Vega et al, 2020 ). The authors showed that Myogenin was deubiquitinated by USP7, favoring Myogenin accumulation in differentiating cells.…”
Section: Ups and The Regulation Of Satellite Cell Functionmentioning
confidence: 99%